1992
DOI: 10.1159/000126236
|View full text |Cite
|
Sign up to set email alerts
|

Central Oxytocin Mediates Inhibition of Sodium Appetite by Naloxone in Hypovolemic Rats

Abstract: Pituitary oxytocin (OT) secretion is inversely related to saline consumption in several experimental models of sodium appetite in rats. Because systemic OT administration does not inhibit sodium appetite, release of OT as a neurotransmitter within the brain, coincident with its secretion from the pituitary, may be related to inhibition of sodium ingestion. The present studies evaluated this possibility by increasing brain OT concentrations both exogenously and endogenously in rats with hypovolemia produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 28 publications
4
21
1
1
Order By: Relevance
“…The OTKO mice also showed elevated intakes after 24 hours of water restriction, a condition that increases both hematocrit and plasma osmolality. 21 These results are supportive of studies in rats that showed that PEG-induced salt intake was inhibited by central OT administration, 9 whereas lesions of the brain OT system increased the response to hyperosmolality. 11 In contrast, an OT antagonist had no effect on PEGinduced salt intake.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The OTKO mice also showed elevated intakes after 24 hours of water restriction, a condition that increases both hematocrit and plasma osmolality. 21 These results are supportive of studies in rats that showed that PEG-induced salt intake was inhibited by central OT administration, 9 whereas lesions of the brain OT system increased the response to hyperosmolality. 11 In contrast, an OT antagonist had no effect on PEGinduced salt intake.…”
Section: Discussionsupporting
confidence: 68%
“…11 In contrast, an OT antagonist had no effect on PEGinduced salt intake. 9 Studies that compared the effect of volume expansion with hypertonic mannitol versus saline showed that saline intake was responsive to osmolality changes, rather than sodium. 11 To proceed to the next stage, we determined whether a stimulus to volume receptors alters salt intake in mice and whether the response is changed in the OT gene-disruption model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, when endogenous oxytocin secretion was stimulated by systemic naloxone, sodium appetite was eliminated (Blackburn et al, 1992b). Similarly, central administration of oxytocin abolished the NaCl intake that accompanies hypovolemiainduced by polyethylene glycol (Blackburn et al, 1992b). These findings provided evidence for oxytocin regulation of salt appetite, but whether such a role for oxytocin fit within the framework of stimulatory signals for sodium consumption remained to be determined.…”
Section: Satiation and Inhibition Of Salt Appetitementioning
confidence: 99%
“…In fact, when endogenous oxytocin secretion was stimulated by systemic naloxone, sodium appetite was eliminated (Blackburn et al, 1992b). Similarly, central administration of oxytocin abolished the NaCl intake that accompanies hypovolemiainduced by polyethylene glycol (Blackburn et al, 1992b).…”
Section: Satiation and Inhibition Of Salt Appetitementioning
confidence: 99%